2014
DOI: 10.1002/acn3.37
|View full text |Cite
|
Sign up to set email alerts
|

Month of birth and risk of multiple sclerosis: confounding and adjustments

Abstract: A month of birth effect on multiple sclerosis (MS) risk has been reported from different countries. Recent critics have suggested that this finding is caused by confounding and that adequately adjusting for year and place of birth would markedly reduce this effect. All inhabitants in Norway are registered in the Norwegian Population Registry (Statistics Norway), making this an ideal area for performing adjusted analyses. Using the entire Norwegian population born between 1930 and 1979 (n = 2,899,260), we calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 6 publications
3
32
1
2
Order By: Relevance
“…For example, the risk of pediatric‐onset MS is increased in association with maternal illness other than diabetes and preeclampsia during pregnancy, and a father with an agricultural profession during pregnancy . Post‐winter birth is more common, and post‐summer birth less common, in people with MS, although there is some debate whether this finding may be due to residual confounding . Lower vitamin D status during pregnancy or infancy is associated with increased risk of MS in Whites …”
Section: Cause Versus Course – Are the Risk Factors Different?mentioning
confidence: 99%
“…For example, the risk of pediatric‐onset MS is increased in association with maternal illness other than diabetes and preeclampsia during pregnancy, and a father with an agricultural profession during pregnancy . Post‐winter birth is more common, and post‐summer birth less common, in people with MS, although there is some debate whether this finding may be due to residual confounding . Lower vitamin D status during pregnancy or infancy is associated with increased risk of MS in Whites …”
Section: Cause Versus Course – Are the Risk Factors Different?mentioning
confidence: 99%
“…Prior studies [4][5][6][7] have demonstrated a higher risk for MS in infants born in the spring, whether in the Northern or Southern hemispheres. Recent work [8][9][10] has questioned these associations based on unaccounted-for biases from birth patterns in the general population. Concern has centered on the concept that birth rates are not homogeneously distributed throughout the year and may vary by region or latitude within a country.…”
mentioning
confidence: 94%
“…Education analysis, however, showed a marked and linear inverse relationship between level of education and the risk of MS in the total study population . Registry data have been included in analyses of month of birth and gender differences in MS incidence .…”
Section: Registry Data In Ms Researchmentioning
confidence: 99%